Answer:
A = (vf - vi) / t <== call this the "given equation "=====================================
For t :Multiply each side of the given equation by 't' : A t = (vf - vi)Divide each side by 'A' : t = (vf - vi) / A=====================================
For vi :Multiply each side of the given equation by 't' : A t = (vf - vi)Subtract ' vf ' from each side: A t - vf = -viMultiply each side by -1 : vf - A t = vi=====================================
For vf :Multiply each side of the given equation by 't' : A t = (vf - vi)Add ' vi ' to each side: A t + vi = vf
Hope it's correct :)